ChemInform Abstract: Ready Synthetic Access to Enantiopure Allylic α(F)‐Branched Fluoroalkenes. Issue 37 (22nd August 2013) - Larnaud, Florent; Malassis, Julien; Pfund, Emmanuel; Linclau, Bruno; Lequeux, Thiery
Abstract For the first time synthesis of homochiral α‐fluorinated benzothiazolyl sulfones (X) with a chiral center in the β‐position is achieved via a Julia‐Kocienski olefination followed by modified Mitsunobu reaction.